Relationship between micronutrient and anemia incidence in adolencents at Islamic boarding school - Kartika Pibriyanti; Lola Zahro; Hafidhotun Nabawiyah (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2020)
ABSTRAKLatar Belakang : Anemia terjadi apabila jumlah sel darah merah berkurang, sehingga kemampuan membawa oksigen keseluruh tubuh akan berkurang. Secara global diketahui prevalensi anemia 1,62 miliar, dimana mayoritas penderita anemia adalah kelompok perempuan yang tidak hamil sebanyak 468,4 juta jiwa. Prevalensi tertinggi anemia adalah kelompok anak-anak perempuan usia sekolah ialah 47,4%, sedangkan pada pria hanya 12,7%. Kebutuhan asupan zat besi pada seorang wanita memiliki kebutuhan yang besar dibandingkan dengan kebutuhan laki-laki.Tujuan: mengetahui hubungan antara asupan mikronutrient (vitamin B6,vitamin B12, vitamin C, zat besi) dengan kejadian anemia pada remaja putri di Islamic Boarding School.Metode: case control dengan matching, kriteria matching yang digunakan umur 15-19 tahun, tidak sedang menstruasi pada saat pengecekan Hb, tidak puasa, dan sudah mengalami menstruasi, pengambilan data dengan cara non-propability yaitu dengan quota sampling. Populasi terdapat 1359 orang dengan sampel 92 orang, case 46 orang control 46 orang, pengambilan data asupan dengan kuesioner Semi Quantitative Food Frequency (SQ-FFQ). Pengujian dengan menggunakan uji statistik 2 berpasangan.Hasil: terdapat hubungan yang signifikan antara asupan mikronutrient (Vitamin C p-value 0,04,OR 1,17,Vitamin B6 p-value 0,0001 OR 3,588, Vitamin B12 (p-value 0,0001)OR 0,27, zat besi (p-value 0,0001) OR 3,091) dengan kejadian anemia remaja di Islamic Boarding School.Kesimpulan: terdapat hubungan yang signifikan antara asupan mikronutrient dengan kejadian anemia pada remaja di Islamic Boarding School.KATA KUNCI: anemia; vitamin B6; vitamin B12; vitamin C; zat besi ABSTRACTBackground : Anemia occurs when the number of red blood cells decreases, so that the ability to carry oxygen throughout the body will decrease. Globally, the prevalence of anemia is 1.62 billion, where the majority of anemia sufferers are women who are not pregnant as many as 468.4 millions of people. The highest prevalence of anemia is that of girls at school age, 47.4%, while for men it is only 12.7%. The need for iron intake in a woman has a greater need compared to the needs of men.Objectives: to determine the relationship between micronutrient intake (vitamin B6, vitamin B12, vitamin C, iron) and the incidence of anemia in adolescent girls in Islamic boarding schools.Methods: Case control with matching, matching criteria used aged 15-19 years, not menstruating at the time of checking Hemoglobin, not fasting, and already experiencing menstruation, data collection using non-probability, namely by quota sampling, the population was 1359 with a sample of 92 people , case 46 people control 46 people, data retrieval with Semi Quantitative Food Frequency (SQ-FFQ) questionnaire. Tests using paired 2 statistical tests.Results: there was a significant relationship between micronutrient intakes (Vitamin C p-value 0.04, OR 1.17, Vitamin B6 p-value 0.0001 OR 3.588, Vitamin B12 (p-value 0.0001) OR 0.27, iron (p-value 0, 0001) OR 3,091) with the incidence of adolescent anemia in Islamic boarding schools.Conclusion: There is a significant relationship between micronutrient intake and the incidence of anemia in adolescents in Islamic boarding schools.KEYWORDS: anemia; iron; vitamin B6; vitamin B12; vitamin C